Kesenangan, Dorongan Berbelanja dan Merek terhadap Intensi Berbelanja Online Produk Fashion (Studi pada Mahasiswi STIE “KBP” Padang) - Febsri Susanti (JURNAL PUNDI, 2017)
The purpose of this study to find out how the influence of pleasure shopping, shopping, brand, the intention to shop through the online shop. The research method used is explanatory research. Sampling technique used ispurposive samplingsehingga from the population are taken as many as 93 respondents. Data analysis technique used is test of validity, reliability, classical assumption test, multiple linear regression test, F test and t test. Based on multiple linear regression analysis, buying pleasure variable, buying impulse, brand to shopping intention through online shop obtained Y = - 0,069 + 0,277 X1 + 0,286 X2 + 0,534 X3Based on the test results simultaneously found that the variable of buying pleasure, buying impulse, brand influence simultaneously to the intention of shopping through online shop with significant value 0,000 <0,05. From the results of partial tests found shopping pleasure variables affect the intention of shopping through the online shop because the resulting significant value of 0.007 <0.05. Shopping boost variables affect the intention of shopping through the online shop because the significant value generated by 0.001 <0.05. Brand variables affect the intention of shopping through the online shop because the significant value generated by 0.000 <0.05. While the results of determination coefficient test obtained Adjusted RSquare with 0.974. This means that the proportion of variance of independent variable to dependent variable is 97,4% the rest of 2,6% explained by other variable not discussed in this research